Utility of serum amyloid A as a potential prognostic biomarker of aneurysmal subarachnoid hemorrhage - Sun, Zhongbo; Li, Yaqiang; Chang, Fu; Jiang, Ke (Frontiers in Neurology, 2023)
Objectives: Inflammation plays a vital role in the aneurysmal subarachnoid hemorrhage (aSAH), while serum amyloid A (SAA) has been identified as an inflammatory biomarker. The present study aimed to elucidate the relationship between SAA concentrations and prognosis in aSAH. Methods: From prospective analyses of patients admitted to our department between March 2016 and August 2022, aSAH patients with complete medical records were evaluated. SAA level was measured by enzyme-linked immunosorbent assay kit (Invitrogen Corp). The Glasgow Outcome Scale (GOS) was used to classify patients into good (GOS score of 4 or 5) and poor (GOS score of 1, 2, or 3) outcome. Results: 456 patients were enrolled in the study, thereinto, 200 (43.86%) patients had a poor prognosis at the 3-months follow-up. Accordingly, patients with poor outcome had obviously higher SAA concentrations (36.44 (IQR 32.23-41.00) vs.28.99 (IQR 14.67-34.12), P＜0.001) at admission compared with those without good outcome. In multivariate analyses, SAA served for independently predicting the poor outcome after aICH at 3 months [OR:1.131 (95% CI, 1.084-1.181), P＜0.001]. After adjusting the underlying confounding factors, the odds ratio (OR) of depression after aSAH was 2.252 (95% CI: 1.100-4.610, P = 0.015) for the highest tertile of SAA relative to the lowest tertile. With an AUC of 0.807 (95% CI, 0.623-0.747), SAA demonstrated an obviously better discriminatory ability relative to CRP, WBC, and IL-6. SAA as an indicator for predicting poor outcome after aSAH had an optimal cut-off value of 30.28, and the sensitivity and specificity were 61.9% and 78.7%, respectively. Conclusions: Elevated level of SAA was associated with poor outcome at 3 months, suggesting that SAA might be a useful inflammatory markers to predict prognosis after aSAH.